Optimization of Deed Printing Services Through the AKUDICARI System at the Population and Civil Registration Office of Badung Regency - Priyanti, Ni Kadek Sukma; Prabawati, Ni Putu Anik (Westscience Press, 2025)
AKUDICARI system is a digital innovation designed to facilitate deed printing services in Badung Regency by providing efficient and transparent online access for the public. The implementation of this system has increased user satisfaction through ease of access, acceleration of the administrative process. This system is designed with the aim that data archives owned by the public can be accessed in real-time. However, there are still significant challenges, especially related to the digital literacy gap and limited technological infrastructure in several areas, especially in rural areas. This study aims to analyze the optimization of services using the AKUDICARI website in civil registration. The method used is a qualitative literature study that analyzes findings from several journals. Efforts to improve digital education, improve internet networks, and develop responsive and inclusive system features are needed to optimize this service. The results of the study indicate that the AKUDICARI system has the potential to become an effective and sustainable digital population administration service model in supporting the digital transformation of government and making people's time more efficient at DISDUKCAPIL.